PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN LIKUIDITAS TERHADAP KINERJA PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR CONSUMER CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Waruwu, Liberni; Indrafana, Iman; Asriadi, Azis (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
This study aims to examine the effect of firm size, leverage, and liquidity on firm performance with dividend policy as a moderating variable. This is a quantitative study that selects a population of consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2024. The sample was selected using a purposive sampling method with five criteria, resulting in 13 companies over five years of observation, totaling 65 samples. Data were collected through documentation study techniques and analyzed using multiple linear regression analysis and residual-based moderated regression analysis (MRA). The results of the analysis indicate that firm size and leverage have no significant effect on firm performance. Liquidity has a significant effect on firm performance. Dividend policy moderates the influence of firm size, leverage and liquidity on firm performance in consumer cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2024